Crazy Talk. (Fortress Press, 2017)
Captivating, entertaining, and highly informative, Crazy Talk helps readers navigate their way through theology that is often confusing and intimidating. This delightful book offers a vocabulary that dares (and equips!) its readers to embrace their own faith in a new, well-informed way. This is a dictionary of theological terms, but with a twist of humor! Each entry includes the name of the theological term, an ironic definition, and a short humorous essay offering a fuller explanation. This revised and expanded edition includes new and expanded entries and all new images.